Respuesta :
Answer:
see explanation
Step-by-step explanation:
Using the rule of exponents
[tex]\frac{a^{m} }{a^{n} }[/tex] = [tex]a^{(m-n)}[/tex], then
[tex]\frac{7^{4} }{7^{-3} }[/tex] = [tex]7^{4-(-3)}[/tex]
His mistake was in subtracting 3 rather than - 3
Andre's mistake was that he was not subtracting the power correctly.
The given expression is,
[tex]\frac{7^4}{7^{-3}}[/tex]
As we know according to the exponent law:
[tex]\frac{a^m}{a^n} =a^{m-n}[/tex]
Now, applying the above law into the given expression we get,
[tex]\frac{7^4}{7^{-3}}=7^{4-(-3)}\\ =7^{4+3}\\=7^7[/tex]
Hence, Andre's mistake was that he was not subtracting the power correctly.
Learn More about the topic Exponents:
https://brainly.com/question/24736882